RANCANG BANGUN SISTEM ANTRIAN DAN PENGOLAHAN DATA REKAM MEDIK PASIEN PADA PUSKESMAS PERTIWI MEMANFAATKAN FRAMEWORK CODEIGNITER - Ian Yo Salli; Syaiful Rahman; Baizul Zaman (KHARISMA Tech, 2021)
The purpose of this research is to apply an algorithm developed in the Intelligent Decision Support System (IDSS) so that it can be reliable data that can be used as a consideration. The benefit of this research is that it becomes an additional reference regarding the use of IDSS in the development of an application. In this study, the authors made a simple video game entitled Gold and Fame to test the algorithm that will be used as a consideration in IDSS. This video game was made with the Unity 5 game engine in the C # programming language. In this study, the authors developed the pathfinding method A * which then provided data for consideration in the IDSS. The results of the algorithm testing by the author show that the use of the developed algorithm is more efficient than the standard so that it can be used as a data processor in IDSS.